Dutch disease, factor mobility, and the Alberta effect: the case of federations - Raveh, O (University of Oxford, 2012)
Do reduced costs of factor mobility mitigate Dutch Disease effects, to the extent that they are reversed? The case of federations provides an indication they do. We observe Resource Blessing effects at the federal-state level (within federations) yet rather Resource Curse ones at the federal level (between federations), and argue the difference in outcomes stems from the difference in factor mobility costs. Through a two-region tax competition model we show that with sufficiently low factor mobility costs a resourceboom triggers an Alberta Effect –where resource abundant regions exploit the fiscal advantage, provided by resource rents, to compete more aggressively in the inter-regional competition over capital, and as a result attract vast amounts of capital– that mitigates, and possibly reverses, Dutch Disease symptoms, so that Resource Curse effects do not apply. Thus, this paper emphasizes the significance of the mitigating role of factor mobility in Dutch Disease theory, and presents a novel mechanism (Alberta Effect) through which this mitigation, and possible reversion, process occurs. The paper concludes with empirical evidence for the main implications of the model.